Optimization of ultrasound-assisted oil extraction from Canarium odontophyllum kernel as a novel biodiesel feedstock - Ideris F.; Shamsuddin A.H.; Nomanbhay S.; Kusumo F.; Silitonga A.S.; Ong M.Y.; Ong H.C.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Biodiesel; Energy utilization; Fatty acids; Feedstocks; Gas chromatography; Hexane; Ionization of gases; Regression analysis; Transesterification; Ultrasonic applications; Box-Behnken experimental design; Fatty acid composition; Flame ionization detection; Physio-chemical properties; Pretreatment process; Response surface methodology; Transesterification process; Ultrasound-assisted extraction; Extraction